2005
DOI: 10.3852/mycologia.97.2.375
|View full text |Cite
|
Sign up to set email alerts
|

Classification of the guava wilt fungus Myxosporium psidii, the palm pathogen Gliocladium vermoesenii and the persimmon wilt fungus Acremonium diospyri in Nalanthamala

Abstract: Psidium guajava wilt is known from South Africa, Malaysia and Taiwan. The fungus causing this disease, Myxosporium psidii, forms dry chains of conidia on surfaces of pseudoparenchymatous sporodochia, which develop in blisters on bark. Similar sporodochia are characteristic of Nalanthamala madreeya, the type species of Nalanthamala. Nalanthamala, therefore, is the appropriate anamorph genus for Myxosporium psidii, while Myxosporium is a nomen nudum (based on M. croceum). For M. psidii the combination Nalanthama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Beyma, Leucosphaerina Arx and Mycoarachis Malloch & Cain as well as the anamorphic genera Acremonium Link, Geosmithia Pitt and Stanjemonium W. Gams et al These fungi form a distinct clade within the Bionectriaceae (Rossman et al 2001, Schroers et al 2005 and are represented by Emericellopsis glabra and Mycoarachis inversa in this study (FIG. 1).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Beyma, Leucosphaerina Arx and Mycoarachis Malloch & Cain as well as the anamorphic genera Acremonium Link, Geosmithia Pitt and Stanjemonium W. Gams et al These fungi form a distinct clade within the Bionectriaceae (Rossman et al 2001, Schroers et al 2005 and are represented by Emericellopsis glabra and Mycoarachis inversa in this study (FIG. 1).…”
Section: Discussionmentioning
confidence: 91%
“…C. coccinea, C. vilior, C. viliuscula and C. wegeliniana) form a monophyletic group within the Nectriaceae. The type species of Acremonium, A. alternatum, belongs in the Bionectriaceae, most closely related to the anamorphic genus Geosmithia, for which no teleomorph is known, and the cleistothecial genera Emericellopsis and Mycoarachis (Rossman et al 2001, Schroers et al 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Schroers & M.J. Wingf. (Schroers et al 2005) was first reported from the Malelane area (Mpumalanga Province of South Africa), in 1981 (Grech 1985;Grech 1990). At that stage the guava industry relied solely on the Fan Retief (FR) cultivar.…”
Section: Introductionmentioning
confidence: 99%
“…Guava wilt, caused by Nalanthamala psidii (Schroers et al 2005) is a serious disease of guava in the guava-producing areas of the Mpumalanga and Limpopo Provinces. Guava wilt disease was first reported in Taiwan by Kurosawa (1926), but is now also present elsewhere in South-East Asia.…”
Section: Introductionmentioning
confidence: 99%